Variability of exotic ginger (Zingiber officinale Rosc.) accessions for quality parameters - Babu, P. Anisha; Leela, N. K.; Venkatesh , J.; Prasath, D. (Journal of Plantation Crops, 2021)
Ginger (Zingiber officinale) is one of the important and widely used spices throughout the world in fresh and dried forms. The study on quality characterization and essential oil profiling of 13 ginger genotypes was conducted at ICAR-Indian Institute of Spices Research, Kozhikode, Kerala, during 2019-2020. The genotypes included eight promising exotic accessions (Acc. 393, Acc. 607, Acc. 736, Acc. 833, Acc. 869, Acc. 872, Acc. 873 and Acc. 874), four popular cultivars (Nadan, Himachal, Maran, Rio-de-Janeiro) and a released variety IISR Varada. Significant differences among the genotypes were recorded for various quality parameters such as oleoresin, essential oil and crude fibre content. Among the exotic genotypes, Acc. 869 recorded the highest essential oil content (2.44%), followed by Acc. 393 (2.42%), Acc. 833 and Acc. 873 (2.10%). The accessions, Acc. 869, Acc. 874, Acc. 873 and Acc. 393 recorded higher oleoresin content of 5.88 per cent, 5.63 per cent, 5.34 per cent and 5.28 per cent, respectively. Considering essential oil and oleoresin contents, the exotic accessions, Acc. 873, Acc. 393 and Acc. 869 were identified as promising genotypes. Among the other genotypes, Rio-de-Janeiro recorded the highest essential oil (2.76%) and oleoresin content (6.69%). The exotic genotypes, viz., Acc. 607, Acc. 736 and Acc. 393 recorded crude fibre content of less than 5 per cent whereas, Acc. 869 recorded the maximum of 7.85 per cent. Fifty compounds were identified through essential oil profiling, and the major classes were sesquiterpene hydrocarbons followed by monoterpene hydrocarbons. The major compound identified was α-zingiberene and was highest in Acc. 393 (30.49%), followed by Maran (30.32%).